Antibacterial activity of Novel PCMX Derivatives (International Journal of Scientific Research in Science and Technology, 2024)
Chloroxylenol, or Parachlorometaxylenol (PCMX), is an antiseptic and disinfectant agent used for skin disinfection and surgical instruments. It is found in antibacterial soaps, wound-cleansing applications, and household antiseptics. Its analogues viz. Ethers, esters and hybrid derivatives also possess various biological activities which prompted us to synthesize a novel analogue for future application as bioactive molecule. These synthesized compounds were tested against certain Gram positive and Gram negative bacterial strains to evaluate their potential antibacterial activity.